Association of stroke lesion shape with newly detected atrial fibrillation – Results from the MonDAFIS study. (September 2022) - Pimentel, Bernardo Crespo; Ingwersen, Thies; Haeusler, Karl Georg; Schlemm, Eckhard; Forkert, Nils D; Rajashekar, Deepthi; Mouches, Pauline; Königsberg, Alina; Kirchhof, Paulus; Kunze, Claudia; Tütüncü, Serdar; Olma, Manuel C; et al.
Paroxysmal Atrial fibrillation (AF) is often clinically silent and may be missed by the usual diagnostic workup after ischemic stroke. We aimed to determine whether shape characteristics of ischemic stroke lesions can be used to predict AF in stroke patients without known AF at baseline. Lesion shape quantification on brain MRI was performed in selected patients from the intervention arm of the Impact of standardized MONitoring for Detection of Atrial Fibrillation in Ischemic Stroke (MonDAFIS) study, which included patients with ischemic stroke or TIA without prior AF. Multiple morphologic parameters were calculated based on lesion segmentation in acute brain MRI data. Multivariate logistic models were used to test the association of lesion morphology, clinical parameters, and AF. A stepwise elimination regression was conducted to identify the most important variables. A total of 755 patients were included. Patients with AF detected within 2 years after stroke ( n  = 86) had a larger overall oriented bounding box (OBB) volume ( p  = 0.003) and a higher number of brain lesion components ( p  = 0.008) than patients without AF. In the multivariate model, OBB volume (OR 1.72, 95%CI 1.29–2.35, p  < 0.001), age (OR 2.13, 95%CI 1.52–3.06, p  < 0.001), and female sex (OR 2.45, 95%CI 1.41–4.31, p  = 0.002) were independently associated with detected AF. Ischemic lesions in patients with detected AF after stroke presented with a more dispersed infarct pattern and a higher number of lesion components. Together with clinical characteristics, these lesion shape characteristics may help in guiding prolonged cardiac monitoring after stroke.